Legal Certainty of The Status of 3 (Three) Kilograms of Gas As A Strategic Goods Free From VAT (Value Added Tax) - Mulyadi Mulyadi (jurnal.unprimdn.ac.id, 2025)
This study aims to examine in depth the normative conflict arising from the enactment of Minister of Finance Regulation (PMK) Number 62/PMK.03/2022 concerning Value Added Tax (VAT) on the delivery of certain Liquefied Petroleum Gas (LPG), specifically subsidized 3 kg LPG cylinders, against regulations that have a higher position in the hierarchy of laws and regulations. The PMK stipulates that the unsubsidized portion of the price of 3 kg LPG is subject to VAT and must be collected by agents down to the base level, which is then passed on to the end consumer. This policy has caused controversy because it conflicts with several higher regulations, such as Law Number 42 of 2009 concerning VAT, Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP), and Presidential Regulation Number 71 of 2015 concerning Determination and Storage of Basic Necessities and Important Goods.Through a normative legal approach, this study sought to obtain the necessary data related to the problem. The data used were secondary data, consisting of primary legal materials, secondary legal materials, and tardier legal materials. In addition, premium data was also used as secondary data. Data analysis was conducted using a normative legal analysis method. This study found that PMK 62/2022 does not align with the principle of the hierarchy of legal norms as proposed by Hans Kelsen, where lower norms must not contradict higher norms.This study concludes that PMK 62/2022 constitutes a form of vertical norm conflict that not only contradicts higher positive law but also contradicts the principles of social justice as stipulated in Pancasila and the 1945 Constitution. Therefore, policy revision or revocation of this regulation is necessary to ensure legal harmony, legal certainty, and protection for vulnerable communities.